Transformational and Ethical Leadership in Islamic Schools: Strengthening Teachers' Professional Ethics and Religious Character among Generation Z Students at MA Subhanah Subah Batang - Affix Ihsan Madani; M. Sugeng Solehuddin; Niken Rahmawati (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study examines the integration of transformational and ethical leadership in strengthening teachers' professional ethics and fostering the religious character of Generation Z students within the Islamic school environment. Employing a qualitative approach with an interpretive single-case study design, the research was conducted at MA Subhanah Subah Batang, Central Java, Indonesia. Data were collected through semi-structured interviews, participant observation, and document analysis, and subsequently analyzed using Reflexive Thematic Analysis. The findings reveal that the integration of both leadership styles produces a holistic organizational ecosystem, conceptualized as the